Thermal Analysis of the Solar Dish Array Concentrator System - Yaseen H. Mahmood; R. Y. J. Al-Salih; Saif Amer Mahdi; Abdelrahman Mohamed Ibrahim (Advances in Materials Science and Engineering)
This research aimed at fabricating solar array concentrator. It is one of the best options for solar energy concentration. Compared with other systems, because of the higher concentration ratios and high control focal length, good accept angles, higher efficiency, rigid with high wind, and low cost, the system has been locally designed and fabricated to produce steam. The dimensions of the active aperture area of 3.25 m2 were studied. The absorber receiver, which conveyed water as heat in a closed cycle with an appropriate pump, produced steam at a higher temperature and with more efficiency. The best characterizations of the system are the focal length 1.25 m, concentration ratio 103, optical power 1.2 kW, losses 0.2 kW, and efficiency 60–70%.